1983
DOI: 10.1111/j.1432-1033.1983.tb07457.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Trimeric, Self‐Recognizing Geodia cydonium Lectin I

Abstract: A D-galactose-specific lectin I was extracted from the sponge Geodia cydonium and purified by affinity chromatography. The molecular weight of Iectin I as determined by high-pressure liquid gel chromatography, was found to be 36500 1300. Disc gel electrophoresis in the presence and in the absence of sodium dodecyl sulfate showed that lectin I is a trimer composed of three different subunits ( M , : 13 800,13 000 and 12200); two of the three subunits are linked by one disulfide bond. Isoelectric focusing gave a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 32 publications
(10 reference statements)
0
13
0
5
Order By: Relevance
“…The purified molecules have an M r of 13-18 kDa (Bretting et al 1981;Müller et al 1983) and bind specifically to the sugars DGalNAc, DGalß1 → 4DGlcNAc, DGal β1 → 3DGlcNAc and DGalNAc (Vaith et al 1979;Bretting et al 1981); the highest specificity has been determined for GalNAcα1-3GalNAc (Forssman disaccharide) and GalNAcα1-3(Fucα1-2)Gal (blood group A; Hanisch et al 1996). In the presence of Ca 2+ , sponge galectins undergo conformational changes and "polymerize" into large three-dimensional clumps (Diehl-Seifert et al 1985b;Fig.…”
Section: Galectinmentioning
confidence: 98%
“…The purified molecules have an M r of 13-18 kDa (Bretting et al 1981;Müller et al 1983) and bind specifically to the sugars DGalNAc, DGalß1 → 4DGlcNAc, DGal β1 → 3DGlcNAc and DGalNAc (Vaith et al 1979;Bretting et al 1981); the highest specificity has been determined for GalNAcα1-3GalNAc (Forssman disaccharide) and GalNAcα1-3(Fucα1-2)Gal (blood group A; Hanisch et al 1996). In the presence of Ca 2+ , sponge galectins undergo conformational changes and "polymerize" into large three-dimensional clumps (Diehl-Seifert et al 1985b;Fig.…”
Section: Galectinmentioning
confidence: 98%
“…cydonium [2, 3], has been sequenced on the protein and DNA levels and shown to exhibit striking homology to the carbohydrate recognition domain characteristic for mammalian galectin‐1 [2, 3]. The lectin molecule binds two moles of lactose per mole of native lectin in a calcium independent manner [4]. Recently, it was shown that GCL binds with high affinity for the blood group A trisaccharide and even more strongly for the Forssman di‐ and pentasaccharides [5].…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the relative molecular mass of the lectin by high-pressure liquid gel chromatography was performed essentially as described earlier [2]. The calibration curve of the molecular mass marker proteins was found to be linear after plotting the ratio between the retention times (tr) and the time for the pressure peak (to) against the logarithm of the M , of the calibration proteins (mentioned in the legend to Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For the analysis of the sugar content in the purified lectin preparation a described procedure [2] was applied.…”
Section: Methodsmentioning
confidence: 99%